Determinasi Faktor-Faktor Yang Memengaruhi E-Loyalty Pengguna E-Commerce Di DKI Jakarta Terhadap Fitur Pembayaran Digital - Bicky Maulana; Osly Usman; Ayatulloh Michael Musyaffi (Jurnal Manajemen Bisnis Era Digital, 2024)
This research aims to determine the factors that influence the e-loyalty of e-commerce users in DKI Jakarta towards digital payment features. In this study there are five variables, namely e-service quality, e-trust, perceived usefulness, e-satisfaction, and e-loyalty with the sample criteria being domiciled in DKI Jakarta, at least 17 years old, and having used the ShopeePay e-wallet for three last month. The research method used is quantitative with purposive sampling data collection techniques. This research produced data from 177 respondents which were analyzed using SmartPLS 4.0 software with the Partial Least Square (PLS) method. The research results show that e-service quality has a positive and significant effect on e-satisfaction, e-trust has a positive and significant effect on e-satisfaction, perceived usefulness has no positive and significant effect on e-satisfaction, e-service quality has no positive and significant effect towards e-loyalty, e-satisfaction has a positive and significant effect on e-loyalty, perceived usefulness has a positive and significant effect on e-loyalty. Furthermore, e-service quality does not have a positive and significant effect on e-loyalty through e-satisfaction, e-trust has a positive and significant effect on e-loyalty through e-satisfaction, and perceived usefulness has a positive and significant effect on e-loyalty through e-satisfaction. satisfaction.